Observational Study of Microbial Colonization and Infection in Neurological Intensive Care Patients Based on Electronic Health Records - Alesya S. Gracheva; Artem N. Kuzovlev; Lyubov E. Salnikova (Biomedicines)
Background/Objectives: Patients with central nervous system injuries who are hospitalized in intensive care units (ICUs) are at high risk for nosocomial infections. Limited data are available on the incidence and patterns of microbial colonization and infection in this patient population. Methods: To fill this gap, we performed an electronic health record-based study of 1614 chronic patients with brain injury admitted to the ICU from 2017 to 2023. Results: Among the infectious complications, pneumonia was the most common (n = 879; 54.46%). Sepsis was diagnosed in 54 patients, of whom 46 (85%) were diagnosed with pneumonia. The only pathogen that showed an association with the development of pneumonia and sepsis in colonized patients was Pseudomonas aeruginosa (pneumonia: p = 7.2 × 10−9; sepsis: p = 1.7 × 10−5). Bacterial isolates from patients with and without pneumonia did not differ in pathogen titer or dynamics, but patients with monomicrobial culture were more likely to develop pneumonia than patients with polymicrobial culture (1 vs. 2 pathogens, p = 0.014; 1 + 2 pathogens vs. 3 + 4 pathogens, p = 2.8 × 10−6), although the pathogen titer was lower in monoculture than in polyculture. Bacterial isolates from all patients and all culture sites showed high levels of multidrug resistance (Gram-negative bacteria: 88–100%; Gram-positive bacteria: 48–97%), with no differences in multidrug-resistant organism (MDRO) colonization and infection rates. Conclusions: Our results highlight the high burden of MDROs in neurological ICUs and provide novel ecosystem-based insights into mono- and polymicrobial colonization and infection development. These findings may be useful for developing strategies to protect against infections.